Modern Methods of Connecting Bone Fragments - A Review of Techniques, Materials and Treatment Results - Haraj, Jan; Bieniek, Maciej; Sobkowiak, Marcin; Dachowska, Sandra; Woźniak, Kinga; Namysł, Maria; Matczak, Simon; Fałczyńska, Aleksandra (Journal of Education, Health and Sport, 2026)
The aim of this paper is to review current and emerging methods of surgical treatment of long bone fractures. Particular attention is paid to features such as fixation stability, protection of the biological environment and the impact of new technologies. Classic techniques, such as locking plates and intramedullary nails, remain the standard, offering comparable treatment results with differences in the frequency of complications. MIPO reduces blood supply destabilization and preserves post-traumatic hematoma, reducing the number of complications. Rapidly developing methods such as 3D printing and robotic surgery enable precise planning and personalization of implants, leading to increased positioning accuracy and reducing radiation exposure. At the same time, there is growing interest in biodegradable implants. Magnesium alloys show osteogenic and angiogenic potential, although their clinical effectiveness depends on controlling the rate of degradation. PLGA polymers are used especially in pediatric traumatology, eliminating the need for metal removal. However, many of the innovations described require further research. Combining classic methods with new technologies allows for individualized treatment and optimized results.